2021
DOI: 10.1002/onco.13930
|View full text |Cite
|
Sign up to set email alerts
|

Physician Communication and Patient Understanding of Molecular Testing Terminology

Abstract: Background. The use of molecular testing in oncology is rapidly expanding. The aim of this study is to determine how oncologists describe molecular testing and whether patients understand the terminology being used. Materials and Methods. Sixty conversations between oncologists and patients about molecular testing were observed and technical terms used were noted by the researcher. Patients were interviewed post-conversation to assess their understanding of the noted technical terms. A patient understanding sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…While we could not assess linguistic abilities due to insufficient information in the NCDB and, although Hispanic ethnicity was not associated with a lack of testing, we contend that patients’ understanding of medical terminology and the purpose of testing were below physicians’ expectations. This disparity is exemplified in an analysis reporting that almost half of the patients could not describe specific terms related to biomarker testing immediately after an explanation by their oncologists . False perceptions toward biomarker testing can be attributed to lower health literacy levels and limited efforts by clinicians to explain comprehensively the importance of testing, both of which can be deterrents for patients with lower educational levels.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…While we could not assess linguistic abilities due to insufficient information in the NCDB and, although Hispanic ethnicity was not associated with a lack of testing, we contend that patients’ understanding of medical terminology and the purpose of testing were below physicians’ expectations. This disparity is exemplified in an analysis reporting that almost half of the patients could not describe specific terms related to biomarker testing immediately after an explanation by their oncologists . False perceptions toward biomarker testing can be attributed to lower health literacy levels and limited efforts by clinicians to explain comprehensively the importance of testing, both of which can be deterrents for patients with lower educational levels.…”
Section: Discussionsupporting
confidence: 70%
“…This disparity is exemplified in an analysis reporting that almost half of the patients could not describe specific terms related to biomarker testing immediately after an explanation by their oncologists. 26 False perceptions toward biomarker testing can be attributed to lower health literacy levels and limited efforts by clinicians to explain comprehensively the importance of testing, both of which can be deterrents for patients with lower educational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Those with genetic disorders are likely to have a different relationship with their providers. [33][34][35] Indeed, more of the variance in behavior in the national sample was accounted for when the analysis included having a genetic disorder or disease related gene. These findings suggest that interventions to improve genomic knowledge will increase the public's engagement in positive genomic health behaviors.…”
Section: Connecting Knowledge With Application To Healthmentioning
confidence: 99%
“…A study found that immunotherapy and targeted therapy based on PM can treat brain metastases [ 57 ]. Genomic and molecular profiling of tumors reveals the function of tumor-derived genetic markers [ 58 , 59 ]. A study relating tumor biology with circulating tumor DNA (tDNA) levels was conducted and showed that patients with solid tumors had genomic alterations detected by plasma tDNA assay.…”
Section: Introductionmentioning
confidence: 99%